Characteristics of Microcosmic Pore Structure in Tuffaceous Sandstone Reservoir - Maolei, Cui; Zhengming, Yang (Physical and Numerical Simulation of Geotechnical Engineering, 2017)
In order to understand the characteristics of tuffaceous sandstone reservoir further, we took the Beizhong area of Hailer Basin as an example, to do some research on microcosmic pore structure and distribution patterns by using constant rate mercury penetration technology. The research indicates that pore radius is basically similar, while throat radius is absolutely different for cores of different permeability. The higher permeability is, the more widely throat distributes, and the higher the proportion of mid-coarse throat is. Compared with common sandstone cores with similar permeability, throat distribution curve has characteristics of lower peak value, wider distribution of throat and higher proportion of mid-coarse throat, which embody serious heterogeneity of tuffaceous sandstone. Although the contribution rate of micro-fine throat increases as increasing the permeability, the contribution rate of throat above micro-fine to permeability is far more than that of micro-fine throat. The study results offer theoretical guide for reservoir evaluation and efficient development of tuffaceous sandstone reservoir.